Modified Qing’ e Pills exerts anti-osteoporosis effects and prevents bone loss by enhancing type H blood vessel formation - Lu, Junjie; Hu, Desheng; Ma, Chen; Xu, Xiaojuan; Shen, Lin; Rong, Jianhui; Zhao, Jia; Shuai, Bo (Frontiers in Endocrinology, 2022)
Objective To explore whether the modified Qing’ e Pills (MQEP) exerts anti-osteoporotic effects and prevents bone loss by enhancing angiogenesis. Methods Network pharmacology was used to assess whether MQEP has a pro-angiogenic capacity and to predict its potential targets. Human umbilical vein endothelial cells were treated with glucocorticoids and MQEP to assess cell viability. The expression of angiotensin II type 1 receptor, angiotensin II type 2 receptor, and angiotensin converting enzyme, which are associated with the activation of the renin-angiotensin-aldosterone system, and the expression of vascular endothelial growth factor and hypoxia-inducible factor 1 alpha, which are associated with the formation of type H blood vessels, were examined by western blot and RT-qPCR. Thereafter, the glucocorticoid-induced osteoporosis model was established and intervened with MQEP. Femur scanning was performed with micro-computed tomography; trabecular spacing, trabecular thickness, and trabecular number were observed and calculated; the expression of nuclear factor-kappa B ligand and osteoprotegerin was detected by ELISA, and the ratio was calculated to evaluate the degree of bone resorption. Finally, type H blood vessels that were highly coupled to osteogenic cells were identified by immunohistochemistry staining and flow cytometry. Results This is the first study to reveal and confirm that MQEP could prevent bone loss in glucocorticoid-induced osteoporosis by promoting the expression of hypoxia-inducible factor 1 alpha and vascular endothelial growth factor, which are highly associated with type H blood vessel formation. In vitro experiments confirmed that MQEP could effectively promote the proliferation of vascular endothelial cells and alleviate glucocorticoids-induced activation of the renin-angiotensin-aldosterone system, thereby reducing vascular injury. Conclusion MQEP exerts anti-osteoporosis effects and prevents bone loss by alleviating vascular injury caused by renin-angiotensin-aldosterone system activation and promoting type H blood vessel formation.